The impact of the negative interest rate policy on bank´s profitability : the portuguese experience - Ramos, Francisco André Coelho (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence